The Influence of Country of Origin and Adherence to Halal Principles on Imported Food Purchasing Decision - Dian Retno Intan; Khairul Fahmi Purba; Wildani Lubis; Nana Trisna Mei Br Kabeakan; Mohd Zaffrie bin Mat Amin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
Indonesia has the largest Muslim population in the world. It would be the largest market for halal products. The huge opportunity is not only a business prospect and market target for Muslim-majority countries but also by non-Muslim countries. In fact, most imported foods in Indonesia comes from countries with a minor Muslim population, such as China, Japan, Thailand, South Korea, and Singapore. Thus, the halal of imported product is in doubt. Furthermore, the Indonesian still not consider the halal aspects of product Hence, it is needed an identification regarding consideration in purchasing decision of imported food product. This study aims to investigate the influence of country of origin and adherence to Islamic principles in imported food purchasing decision. A survey was carried out to 205 Muslim people residing in some capital cities in Sumatra Island which were Aceh, Padang, Palembang, and Medan. Data was collected through both offline and online questionnaires. Structural Equation Model – Partial Least Square was applied as data analysis for this study. The study found that country of origin and religiosity have a positive and significant influence on purchasing decisions for imported food products. Furthermore, this study also found that the awareness of halal may act as a mediating variable for religiosity in the purchase decision of imported food products. It implies that the awareness of halal is crucial for Indonesian Muslim consumer. Therefore, the Indonesian Muslim consumers need to improve the knowledge in recognizing halal values and principles for the imported food product.